Dynamic output feedback based robust controller design for selective catalytic reduction systems. (4th April 2022) - Wang, Baigeng; Li, Shurong
Selective catalytic reduction (SCR) is an effective way to deal with the flue gas at the outlet of coal-fired boiler. The working process of SCR systems is to use the ammonia (NH3 ) adsorbed on the catalyst to react with nitrogen oxide (NOx ) to generate nitrogen and water. This paper presents an observer based dynamic output feedback control for SCR systems. Since NH3 coverage ratio cannot be measured directly, a reduced order observer is designed first. And then it is proved that the error of observer tends to 0 by using Lyapunov function. Furthermore, the dynamic equation of the composite including the observer state is obtained. Finally, the controller is designed to adjust the rate of NH3 injection in order to satisfy the industrial demand.